Inflation and Efficiency in Search Markets - Benabou, Roland (Review of Economic Studies, 1992)
This paper examines how inflation affects efficiency and output in monopolistically competitive search markets. It formalizes the conventional wisdom linking higher inflation, price dispersion, and increased resources devoted to search. It also brings to light the induced exit of firms, which reduces rent dissipation. But the most important effect of inflation is how it alters the distribution of real transactions prices. Whether this reduces or promotes efficiency and output is also shown to depend critically on preferences and market structure, and especially on whether search costs are large or small relative to consumer surplus. Copyright 1992 by The Review of Economic Studies Limited.